Assessment of dexterity and diagnostic accuracy of the Functional Dexterity Test in patients with carpal tunnel syndrome - Sartorio, Francesco; Vercelli, Stefano; Bravini, Elisabetta; Zanetta, Anna; Bargeri, Serena; Pisano, Fabrizio; Ferriero, Giorgio (La Medicina del Lavoro, 2018)
Background: The diagnosis of carpal tunnel syndrome (STC) is centered on the symptoms. However, patients also show an impairment of sensorimotor functions, but the relationship between STC and manual dexterity has never been investigated. Objectives: To analyze the correlation between manual dexterity and severity of the STC. Another objective was the diagnostic accuracy of the clinical battery including provocative tests (Phalen, Tinel) and Functional Dexterity Test (FDT). Methods: A sample of 80 subjects with suspected STC was subdivided into 4 groups based on EMG (severe/extreme-GrA, moderate-GrB, mild/minimal-GrC, negative-GrD) and evaluated in blind by Phalen, Tinel and FDT. The relationship between the FDT and the allocation of subjects was investigated by Spearman’s rho, while the groups were compared with univariate ANOVA and Tukey’s post hoc analysis. Diagnostic accuracy of the clinical battery was expressed by sensitivity, specificity, and likelihood ratios (LR). Results: A moderate (r=0.48, p